Dry Anaerobic Digestion of Brewer’s Spent Grains toward a More Sustainable Brewery: Operational Performance, Kinetic Analysis, and Bioenergy Potential - William Gustavo Sganzerla; Josiel Martins Costa; Miriam Tena-Villares; Luz Selene Buller; Solange I. Mussatto; Tania Forster-Carneiro (Fermentation, 2022)
Industrial beer production generates brewer’s spent grains (BSG) as a primary solid waste. The disposal of industrial waste can cause negative environmental side effects, including greenhouse gas emissions. This study evaluated the dry anaerobic digestion (AD) of BSG for bioenergy recovery as a solution toward a more sustainable brewery. The laboratory-scale agitated tank batch reactor (6.8 L) was started up with BSG (25%), mesophilic inoculum (45%), and water (30%). The experimental results showed 82.12% solids biodegradation, 57.38% soluble chemical oxygen demand removal, and an accumulated methane yield of 10.53 L CH4 kg−1 TVS. The methane production efficiency was evaluated by the modified Gompertz, Cone, and first-order kinetic models. The Cone model fitted methane evolution better than the modified Gompertz and first-order kinetic models. The biogas produced from the dry AD of BSG could generate electricity (0.133 MWh ton−1) and heat (598.45 MJ ton−1), mitigating 0.0099 and 0.0335 tCO2eq ton−1 BSG, respectively, for electricity and heat. The implementation of dry AD could supply 7.38% of the electricity and 6.86% of the heat required for beer production. Finally, in a biorefinery concept, dry AD can be an alternative route for solid waste management and bioenergy recovery, contributing to reduce the environmental impact of breweries.